A Cross-Sectional Study on the Prevalence of Diseases among the Geriatric Population in the Rural Field Practice Areas of a Tertiary Care Hospital in Mangaluru, India - Venkateshkrishna, Narayana; Suresh, Sucharitha (Journal of Pharmacy Practice and Community Medicine)
Background: Population ageing is a universal and inevitable phenomenon. Hence, it is necessary to understand the disease burden among the elderly in our rural field practice areas and a demographic survey was conducted to know the common diseases prevailing among them. Objectives: To know the common diseases among the elderly population 60 years and above and to assess the Prevalence of these diseases and to improve the quality of life of the elderly and also to treat them. Methodology: A community based study was conducted in the rural areas of Bollary, Jarandagudde, Mundaje and Ammunje which comes under the field practice areas of Father Muller MedicalCollege, Mangaluru, Karnataka, India between June 2014 to May 2015. All the elderly people who visited these Centers during that period were included in the study. The data was allocated from the records kept in the out-patient departments of these health centers. Results: A total of 1452 elderly people were examined in the study. Among them 530(36.50%) were males and 922(63.50%) were females participated in the study. Most of the elderly were suffering from hypertension (37.67%), diabetes (5.99%) both hypertension and diabetes (9.02%), while acid peptic disease (5.51%) and other complaints (45.52%), were also seen. Conclusion: Non-Communicable diseases like hypertension and diabetes were more compared to acid peptic disease, other complaints like fever, cough and cold, breathlessness were effecting the elderly population. Thus it is necessary to do an early diagnosis and treatment.
Keywords: Elderly population; Hypertension; Diabetes; Acid peptic disease; Other Complaints